Geographies of digital exclusion : data and inequality - Graham, Mark, 1980-; Dittus, Martin (Radical geography., 2021)
Graham and Dittus look at the key contours of information inequality, and who, what, and where gets left out when space becomes digital. Platforms like Google Maps and Wikipedia have become important gateways to understanding the world. This book reveals how these platforms are characterised by significant gaps and biases, often driven by processes of exclusion. As a consequence, their digital augmentations tend to be refractions rather than reflections: they highlight only some facets of the world at the expense of others. However, this doesn't mean that more equitable futures aren't possible. By outlining the mechanisms through which our digital and material worlds intersect, the authors conclude with a roadmap for what alternative digital geographies might look like. --From publisher description.